KONSELING PERKAWINAN/KELUARGA ISLAMI - Syahraeni, Andi (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2014)
Marriage can be called to uniting the two uniqueness. Differences in temperament, character, taste and knowledge of two people who are united in the household, living together in a long time. .Some households problems that need counselor in solving problem among others: economic problems that can create tension in the family, differences in temperament and character and personality are too sharp differences between husband and wife are difficult to find common ground, the bustle of a husband whose wife more outside and infidelity. Similarly educational inequalities between husband and wife , saturation routine especially wife who had no activities outside the home and the main thing is because it is far from religion .The purpose of counseling on marital and Islamic family is to solve problems are facing a family whether husband or wife and his sons and clients can independently make the decision.